Questioning gender : a sociological exploration - Ryle, Robyn (Sage, 2018)
"With content organized around big questions about gender, Questioning Gender: A Sociological Exploration serves as a point-of-departure for conversations about gender, and as a resource for exploring answers to many of those questions. Rather than providing definitive answers, this unique book exposes readers to new material that will lead them to question their assumptions." --Amazon.com.